Pumps and pipes proceedings of the annual conference - Davies, Mark G. (Springer, 2011)
The Pumps and Pipes collaboration and conference brings together energy, medicine, and higher education in a unique shared effort, exploring ideas and research common to these important fields and stimulating discussion and sharing technologies that can further the reach and goals of each individual area. ?Pumps and Pipes? explores the common attributes of oil and gas technology, computational sciences and cardiovascular medicine and probe the areas where there is room to cross-fertilize and develop research and commercial programs. This proceedings also: Offers a unique perspective on the collaboration between medicine, petroleum technology and computational science Contributors include researchers from world class institutions such as the Methodist Debakey Heart and Vascular Center, Exxon Mobil Research, University of Houston, the Texas Heart Institute, Schlumberger Corporation and others Discusses the cross-disciplinary nature of hydraulics conduits and pumps, atherosclerosis, corrosion and scale management, piping and stenting "Pumps and Pipes" is the perfect book for researchers and engineers working in mechanical and materials engineering.